A new species of Protosticta Selys, 1885 (Odonata: Zygoptera: Platystictidae) from Western Ghats, Kerala, India - K. G. Emiliyamma; Muhamed Jafer Palot (Journal of Threatened Taxa, 2016)
A new species of Protosticta Selys, 1885 from Kerala part of Western Ghats is described and illustrated.  The holotype male and paratype female is distinguished from other Protosticta species based on its complete black dorsal surface of abdomen, 7th and 8th abdominal segment without yellow or blue color dorsally and its distinct anal appendages.  The new species, Protosticta monticola sp. nov. was collected from shola forests of Idukki District, Kerala, southern Western Ghats.  A key is also provided for the identification of all described species of Protosticta known from the Western Ghats.